Development and Analysis of Investment Strategies in Energy Efficiency for Ukrainian Household Prosumers - Olha Prokopenko; Yevhen Kovalenko; Svitlana Lytvynenko; Dmytro Riabtsev (Vasyl Stefanyk Precarpathian National University, 2024)
This article explores the development and analysis of investment strategies in energy efficiency for Ukrainian household prosumers using an econometric model. The study identifies key determinants influencing investment decisions by prosumers, such as income levels, energy prices, government subsidies, environmental awareness, technology adoption, urbanization, and education. By employing an econometric model, the research provides robust insights for policymakers, energy industry stakeholders, and prosumers themselves to enhance energy efficiency and promote sustainable energy practices in Ukraine. The analysis covers the period from 2019 to 2023 and focuses on secondary data sources, including government reports, energy industry publications, and academic studies. The econometric model includes fixed effects and random effects to account for unobserved heterogeneity and panel-specific effects, with lagged dependent variables and instrumental variables to address endogeneity. Results show that higher income levels, government subsidies, environmental awareness, technology adoption, urbanization, and education positively influence investment in energy efficiency by prosumers. Energy prices have a negative impact, likely due to cost concerns. Case studies of successful prosumer investment strategies, such as solar panels, energy-efficient appliances, smart home technologies, and insulation/weatherization, further demonstrate the feasibility and benefits of energy efficiency investments. These findings offer valuable insights for policymakers and stakeholders to support prosumers in making informed and sustainable investment decisions, ultimately contributing to a more energy-efficient and sustainable future for Ukraine. The research highlights the need for consistent policy support to sustain investment momentum, especially in the context of the current war and its impact on Ukraine's energy infrastructure. Additionally, it underscores the importance of rebuilding and enhancing the country's energy systems in the post-war recovery phase to ensure long-term sustainability.